Implantable cardioverter defibrillator: decision-making on turning off in patients with end-stage heart failure - V. K. Lebedeva; D. S. Lebedev (Российский кардиологический журнал)
The use of implantable cardioverter defibrillators has become a common standard method of primary and secondary prevention of sudden cardiac death, prolonging the life of patients with cardiomyopathy. At the same time, with the disease and comorbidity progression, at the final stages of life, a difficult decision arises to turn off the device due to a shift in priorities from extending life to maintaining its quality. Heart failure patients eventually die due to the progression of the underlying disease, despite currently available advanced technologies. Whether certain lifesustaining treatment methods are still appropriate in the final stages of life is an important topic of discussion in this article. Palliation for patients with implantable cardioverter-defibrillators is a challenging issue for both patients and medical professionals. This article describes the different ways to turn off defibrillation devices based on patient status.